Date Of Easter Sebagai Reformasi Kalender Masehi - Jannah, Elly Uzlifatul (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
This research discusses the history of the calculation of the date of Easter as part of the reform of the Gregorian calendar using a historical approach. It examines the history of the determination of the date of Easter by the Council of Nicaea in 325 AD and the use of the ecclesiastical full moon method to calculate the date of Easter. This research also discusses the differences in the dating of Easter in the Julian and Gregorian calendars and the relationship between the dating of Easter and the astronomical vernal equinox. The results of this research show that the date of Easter is calculated based on mathematical calculations, taking into account the ecclesiastical full moon and is no longer related to accurate astronomical calculations. This research provides a clear overview of the history and methods of determining the date of Easter and can serve as a reference for scientists and researchers to further study the reform of the Gregorian calendar and the calculation of the date of Easter.